Clinical pharmacy services in Germany: a national survey - Schulz, Claudia; Fischer, Andreas; Vogt, Winnie; Leichenberg, Katja; Warnke, Ulrich; Liekweg, Andrea; Georgi, Ulrike; Langebrake, Claudia; Hoppe-Tichy, Torsten; Dörje, Frank; Knoth, Holger (European journal of hospital pharmacy, 2021)
Objectives: Clinical pharmacy services in German hospitals appear to be underdeveloped compared with other European countries. However, recent developments have increased the interest in expanding these services. Detailed data about the current state of clinical pharmacy services in Germany are lacking. This survey establishes the current level of pharmacy services in Germany and the barriers to implementation. - Methods: An online survey conducted in 2017 was distributed to directors of all 389 German hospital pharmacies. The survey contained 26 questions addressing hospital and pharmacy characteristics, clinical pharmacy services provided, the number of clinical pharmacists and the frequency as well as the quality assurance of these services. - Results: There were 133 responses (34%). Of these, 84 (63%) pharmacies provided some form of clinical pharmacy services. Based on the 389 contacted pharmacies, a clinical pharmacy service is available in at least 22% of hospital pharmacies in Germany. On average there are 2.4 full-time equivalent (FTE) clinical pharmacists per hospital employed, although there is a wide variation in numbers (0.3-22 FTE) and service provision between hospitals. Clinical pharmacy services are generally provided on a daily or weekly basis, with a principal focus on general surgery, critical care and general medicine wards. - Conclusions: This is the first survey providing a detailed picture of clinical pharmacy services in Germany. There is wide variation in clinical service provision among hospitals, with some hospitals having developed a comprehensive range of clinical services. Compared with other countries, particularly the UK where the focus has shifted to provision of 7-day clinical services, the gap in clinical pharmacy services remains large. The focus should be turned to refining clinical pharmacy services in hospital admissions and discharge planning while also improving Health IT, the opportunities for specialisation and aligning education in accordance with the EAHP common training framework.
Gesehen am 15.12.2021